Myocardial Dystrophy In Chronic Obstructive Pulmonary Disease: Mechanisms Of Development, Early Markers, And Treatment Approaches (Texas Journal of Medical Science, 2026)
This article examines the relationship between chronic obstructive pulmonary disease (COPD) and myocardial dystrophy, focusing on pathophysiological mechanisms, diagnostic approaches, and therapeutic strategies. A total of 120 COPD patients were evaluated for myocardial dysfunction using echocardiography, cardiac biomarkers (NT-proBNP, troponin I, CK-MB), and inflammatory markers (IL6, TNF-α, CRP). The results demonstrated that myocardial dystrophy is present in 68.3% of COPD patients, with severity correlating with disease stage. Hypoxia-driven oxidative stress and systemic inflammation were identified as the primary mechanisms. Combined bronchodilator therapy supplemented with cardioprotective agents (trimetazidine 35 mg twice daily) significantly improved both pulmonary and cardiac functional parameters.